Modern Diagnostic Aspects of Fractures of the Naso-Zygomatic-Orbital Complex - Sh.A. Yusupov; Sh.A. Boymuradov; B.K. Narmurotov; J.A. Djuraev; I.O. Nigmatov (International Journal of Medical Toxicology and Legal Medicine, 2024)
This article presents the results of diagnostic aspects and planning of surgical treatment of patients with fractures of the zygomatic-orbital complex. Despite the large number of works devoted to this topic, the literature data concerning the choice of diagnostic methods and planning of surgical treatment are rather fragmentary and not systematized, which in turn allows us to focus activities and research on the development and modernization of methods for diagnosing and surgical treatment of fractures of the zygomatic-orbital complex. In this study, the features of fractures of the zygomatic-orbital complex in 117 patients were studied using modern radiological diagnostic methods. The results of our studies showed that the prevalence of isolated damage to the lower wall of the orbit is 29.3%.